Effects of otter board and cable length on hydrodynamic performance of Antarctic krill trawl system. (15th September 2021) - Wan, Rong; Guan, Qinglong; Huang, Liuyi; Li, Zengguang; Zhou, Cheng; Wang, Lei; Jia, Mingxiu
Abstract: The net position and the spreading performance are crucial for hydrodynamic performances of Antarctic krill trawl, which determine its fishing efficiency. In this paper, the hydrodynamic performance of an Antarctic krill trawl system (including trawler, cable, otter board and trawl) was studied by means of numerical simulation combined with full-scale measurement at sea. The numerical model was established based on finite element method and the principle of minimum potential energy was employed to determine the equilibrium configuration of the trawl system in uniform current. The Newton–Raphson method was applied to solve the equilibrium equation. A multi-wing vertical cambered otter board was designed and a series of wind tunnel model tests were carried on in order to explore the hydrodynamic performance (drag coefficient, lift coefficient and lift-drag ratio) of the otter board. By comparing the simulated results and the simulated results after correction with the experimental results at sea, the modified Tauti's law and the accuracy of the numerical method were verified. The results showed that the fishing vessel, the trawl and the otter board matched well on hydrodynamics. The effects of the warp length, the leg length, the towing speed and the angle of attack of the otter board on the net position, the spread of otter board and the spreading performance of net opening were analyzed. Scientific suggestions on the setting of each component of the trawl system were given based on the numerical simulation study. This paper could be regarded as a scientific reference for Antarctic krill trawl fishing operation. Highlights: A multi-wing vertical cambered otter board is designed. Study on hydrodynamic performance of Antarctic krill trawl system. Verifying the accuracy of numerical simulation and modified Tauti's law. Study the effects of otter board and cable length on the performance of krill trawl.